Recommendations for the aesthetic evaluation of breast cancer conservative treatment - Machado, Maria João Cardoso Vieira; Heil, Jörg (Breast cancer research and treatment, 2012)
During the Turning Subjective Into Objective seminar held in Lisbon in May 2011, experts in the topic gathered to discuss the unsolved problems of aesthetic evaluation of breast-conserving treatment (BCT). The purpose of this study is to review the main methodological issues related to the aesthetic evaluation of BCT, to discuss currently used methods of evaluation and the lack of a gold standard, and to write a set of recommendations that can be used as guidance for the aesthetic evaluation of BCT.